Smart Agriculture, Precision Agriculture, Digital Twins in Agriculture: Similarities and Differences - Alakuş, Dilan Onat; Türkoğlu, İbrahim (Institute of Electrical and Electronics Engineers Inc., 2024)
Agriculture has always been the main source of livelihood for humanity. The agriculture sector is undergoing a major transformation with industry 4.0 and big data technologies. Smart agriculture, precision agriculture and digital twins in agriculture are the main technologies that enable this transformation. Although the aim of these technologies is to ensure product quality, productivity and sustainability in agriculture, they differ in terms of the way they are applied and their capabilities. This study provides a perspective for understanding modern agricultural techniques by exploring the similarities and differences of smart agriculture, precision agriculture and digital twin technologies in agriculture. To understand these three technologies, twenty-one questions covering their technological infrastructure and capabilities were prepared and analyzed. The similarities and differences of these technologies are presented in the conclusion section. © 2024 IEEE.
2024 Innovations in Intelligent Systems and Applications Conference, ASYU 2024 -- 16 October 2024 through 18 October 2024 -- Ankara -- 204562
Keywords: digital twin in agriculture; precision agriculture; smart agriculture